THE POTENTIAL DEVELOPMENT STRATEGY OF PESANTREN LITERATURE TO SUPPORT A RELIGIOUS TOURISM TOWARDS A CREATIVE INDUSTRY (English Education Journal, 2011)
Pesantren's literature is a cultural treasure which exists in Indonesia. Pesantren'senchantment can be viewed from many sides; i.e. environment, education, teaching, human,even customs and arts. These conditions provide a variety of potential to be optimized. Theaim of this study is to expose the potential and model of pesantren's literature to supportreligious tourism as a creative industry. The result of this study is to optimize the potentialdevelopment strategy of pesantren's literature and to support religious tourism as a creativeindustry. Pesantren's literature is used as one of religious tourism attractions that brings theeconomic life towards a creative industry, and to create other economic activities beneficialfor the grassroots' level.